2012
DOI: 10.1074/jbc.m111.330902
|View full text |Cite
|
Sign up to set email alerts
|

Highly Aggregated Antibody Therapeutics Can Enhance the in Vitro Innate and Late-stage T-cell Immune Responses

Abstract: Background: Aggregated biotherapeutics have the potential to induce an immune response.Results: Aggregates can enhance innate and adaptive immune responses of PBMC.Conclusion: The response depends on aggregate type, immunogenicity of the monomer, donor immune status, and high particle numbers in the in vitro assay.Significance: This is the first study showing the impact of aggregate characteristics on the potential immune response of PBMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
276
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(299 citation statements)
references
References 61 publications
21
276
2
Order By: Relevance
“…11 In vitro techniques seem to have more predictive potential in this field and are currently being explored for studying formulation-related immunogenicity, including the role of aggregates. 10,23 In contrast, methods for in vivo prediction include the entire immune machinery and environment necessary to better simulate the extremely complex scenario that results in complete immune responses, especially when protein aggregates are involved. Thus, currently the use of animal models to predict immunogenicity in vivo seems to be the most promising approach to predict aggregate-related ADA responses.…”
Section: Size Exclusion Chromatography (Sec) It Is Clear Frommentioning
confidence: 99%
“…11 In vitro techniques seem to have more predictive potential in this field and are currently being explored for studying formulation-related immunogenicity, including the role of aggregates. 10,23 In contrast, methods for in vivo prediction include the entire immune machinery and environment necessary to better simulate the extremely complex scenario that results in complete immune responses, especially when protein aggregates are involved. Thus, currently the use of animal models to predict immunogenicity in vivo seems to be the most promising approach to predict aggregate-related ADA responses.…”
Section: Size Exclusion Chromatography (Sec) It Is Clear Frommentioning
confidence: 99%
“…16 Such irreversible aggregates can decrease protein activity and stability, and may elicit adverse immunogenic reactions in patients. [17][18][19] In addition, parenteral administration of highly viscous liquids requires thicker gauge needles that may cause more painful injections. 2 Previous work has shown that reversible self-association (RSA) between different IgG1 mAbs can result from different binding interfaces, despite high sequence similarity between the mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregates in the size range of 0.1-10 µm are believed to be the most immunogenic (33). Recently, new animal testing methods have been developed that together with in-silico predication models, can provide additional help to explain potential immunogenicity (34,35).…”
Section: Unwanted Immunogenicity Of Biologicals That Contain Monoclonmentioning
confidence: 99%